2017
DOI: 10.1093/neuros/nyx250
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Safety of Intramedullary Transplantation of Human Neural Stem Cells in Chronic Cervical and Thoracic Spinal Cord Injury

Abstract: A total cell dose of 20 M cells via 4 and up to 40 M cells via 8 perilesional intramedullary injections after thoracic and cervical SCI respectively proved safe and feasible using a manual injection technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 38 publications
1
88
0
Order By: Relevance
“…Banked NSCs can also induce functional myelin in a severe demyelination model (Uchida et al., 2012), the shiverer mouse, and restore motor function in a mouse model of spinal cord injury ( Cummings et al., 2005, Salazar et al., 2010). The proof-of-concept data in pre-clinical studies led to other phase I or II studies with NSCs in the hypomyelinating disease, Pelizaeus-Merzbacher disease (PMD) (Gupta et al., 2012), traumatic thoracic and cervical spinal cord injury (Levi et al., 2017), and age-related macular degeneration (clinical trial number NCT01632527). These clinical studies demonstrated the safety, feasibility, long-term survival, and early evidence of efficacy of using banked NSCs in treating neurologic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Banked NSCs can also induce functional myelin in a severe demyelination model (Uchida et al., 2012), the shiverer mouse, and restore motor function in a mouse model of spinal cord injury ( Cummings et al., 2005, Salazar et al., 2010). The proof-of-concept data in pre-clinical studies led to other phase I or II studies with NSCs in the hypomyelinating disease, Pelizaeus-Merzbacher disease (PMD) (Gupta et al., 2012), traumatic thoracic and cervical spinal cord injury (Levi et al., 2017), and age-related macular degeneration (clinical trial number NCT01632527). These clinical studies demonstrated the safety, feasibility, long-term survival, and early evidence of efficacy of using banked NSCs in treating neurologic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…One clinical trial reported one subdural hematoma in 18 patients who underwent intraparenchymal stem cell transplantation using the Pittsburg cannula [6] and one in 13 patients who underwent intraparenchymal human neural stem cell transplantation [8]. In contrast, Levi et al showed no needle (30-gauge) complication when injecting human CNS stem cells in 29 patients with cervical and thoracic cord injury, with four to eight sites and a depth of 3-4 mm from the spinal cord surface being selected for injection [16]. However, the possibility of intraparenchymal hemorrhage caused by the injection cannula should not be underestimated, as it may cause catastrophic complications.…”
Section: Discussionmentioning
confidence: 99%
“…The trials were terminated early in 2016; according to a recent report, there was no significant increase in the rate of serious adverse events with escalating doses, suggesting that the therapy was well tolerated. 105 Neuralstem Inc. is now recruiting for an open-label, single-site phase I (N = 8; NCT01772810) safety study of human spinal cord-derived NSCs in individuals with 1-to 2-yearold AIS grade A injuries at C5-7 or T2-12. Results are expected in 2022.…”
Section: Neural Stem Cellsmentioning
confidence: 99%